Technosociality in the daily lives of primary care professionals and health promotion: scoping review - Silva,Tamires Carolina (2021)
ABSTRACT This study aimed to map the available evidence on technosociality in the daily lives of primary care professionals to promote the health of people/families. This is a scoping review based on the Joanna Briggs Institute and Prisma-ScR. The PCC strategy (participants, concept and context) was used. The sample comprises 25 articles. The predominant language was English, the year, 2018, the strength of evidence, 5 and the quality of evidence, high and moderate. Technologies are part of the daily life of PHC professionals and include health control, curative and medication measures. They are sources of communication between professionals and professionals and users. For the use of technologies, it is essential that professionals are trained, using evidence-based practices to achieve the objectives in view of the needs of each one. The use of technologies to promote the health of people/families represents a technological innovation in Primary Health Care, with the possibility of impacting health conditions and promoting healthier life choices.